2017
DOI: 10.1111/all.13142
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated airway hyperresponsiveness and mucus secretion in HDM‐exposed Igf1r‐deficient mice

Abstract: Herein, we demonstrate by the first time that the Igf1r plays an important role in murine asthma, mediating both AHR and mucus secretion after HDM exposure. Thus, our study identifies IGF1R as a potential therapeutic target, not only for asthma but also for hypersecretory airway diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 44 publications
7
35
0
Order By: Relevance
“…RNA isolation and qRT-PCR was performed using inferior lung lobes, as previously described [ 12 ]. A full list of primer sets used is provided in S1 Table .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA isolation and qRT-PCR was performed using inferior lung lobes, as previously described [ 12 ]. A full list of primer sets used is provided in S1 Table .…”
Section: Methodsmentioning
confidence: 99%
“…In mice, IGF1 was reported to be a relevant mediator of allergic airway inflammation and remodeling, and that IGFBP3 blocks the specific physiological consequences of this pathology [ 8 10 ]. Notably, we have recently reported that IGF1R plays an important role in initiation of the inflammatory response in mice, and the importance of IGF1R in the pathogenesis of murine asthma, mediating both AHR and mucus secretion after chronic HDM exposure [ 11 , 12 ]. Thus, we aimed to further investigate the involvement of IGF1R in allergic airway inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Those reasons explain why this protocol has recently been replicated or adapted so many times in the literature. 71 – 76…”
Section: Introductionmentioning
confidence: 99%
“…In the C57BL/6 strain, a type 2 inflammatory response is usually more difficult to achieve as it is skewed towards type 1. However, the strong infiltration of eosinophils into the lungs and the BALF was convincing (Piñeiro-Hermida et al, 2017).…”
Section: Characterisation Of Balf Oxylipins After 4 Weeks Of Hdm Expomentioning
confidence: 98%